Augmented reality as a participation tool for youth in urban planning processes: Case study in Oslo, Norway - Reaver, Kai (Frontiers in Virtual Reality, 2023)
Augmented reality (AR) allows for objects to be digitally simulated in the real world through smartphones, tablets, and headsets. While AR technology has interesting use cases for participatory urban planning, this type of research has yet to be conducted within a real-life municipal planning scenario. Following the UN Habitat recommendation that further studies in AR as a participatory tool seek to integrate planning with real citizens, we studied the use of AR for the Oslo Trees plan in Norway. The case study consists of field work with AR between 2020 and 2021 over 5 weeks, with 5 different groups of youth participants from 8 different districts of Oslo, who were tasked with planning a portion of Oslo’s 100 000 new trees. We document the youth using AR through films, images, drawings, interviews, screen recording, and recorded presentations. We find that AR was a highly intuitive tool for the youth user groups in design and planning, and document that the AR schemes impacted the final design of the plan. The use of AR aided users’ ability to generate their own planning proposals on site at scale, and nearly all participants increased their understanding of participation, urban planning, architecture and design the workshops. In addition, the youth experienced an increased sense of confidence in displaying their design intentions, appreciated being given control of the planning process. However, we also find that location tracking and positioning in AR is imprecise and often buggy in the current state of the technology, causing irritation among users. Also, despite the high degree of control afforded to users through AR, experts were still needed to verify which tree proposals were viable, offering important insight into how AR could be designed in the future. We conclude with a discussion on opportunities and barriers for the implementation of AR into participatory urban planning, pointing to the need for a more coordinated and holistic approach to both AR technology development and planning policy if AR is to be to developed further for participatory urban planning.